Industry currency and vocational teachers in Australia: what is the impact of contemporary policy and practice on their professional development?. Issue 1 (2nd January 2019) - Schmidt, Teressa
ABSTRACT: The quality of vocational education and training (VET) and, in particular, the quality of VET teaching, is a prominent topic of discussion in Australia's post-compulsory education sector. VET teachers are described as 'dual professionals', and expected to maintain current vocational competencies (industry currency) as well as pedagogical skills for effective VET teaching practice. This paper examines issues associated with industry currency activities for Australian VET teachers. It reports on findings from a qualitative study which employed a multiple case study methodology to examine advanced skills for VET teachers. Emergent findings suggest that while legislation requires VET teachers to maintain current vocational competencies as well as knowledge and skills for effective VET teaching, interpretation of policy into practice has led to an unbalanced approach which emphasises industry currency activities over pedagogical skills development. Further, teachers reported difficulty completing currency requirements due to competing pressures of time and teaching commitments, and some industry currency activities regarded as legitimate by VET managers and auditors appear to offer limited developmental opportunities for VET teachers while other activities were overlooked. This is a significant issue which requires further investigation due to its potential impact on VET teacher development and the quality of VET teaching.